Propuesta de modelo de gestión del talento humano para la empresa Óptica Econogafas Internacional de la ciudad de Loja. - Romero Montaño, Cinthya Johana (2024)
This paper entitled, Proposal of a Model for the Human Resources Management in the International Optical Company from the City of Loja, aims to develop a diagnosis of the company’s current situation to later adapt the proposal so that it meets its needs. Its current personnel are considered the area of study, applying a descriptive deductive research methodology. To collect information on the management of personnel in the organization, 6 surveys were applied to the company's employees and an interview with the owner, which are fundamental instruments for data collection that made possible the choice of Idalberto Chiavenato's Management Model as a guide for the design of the proposal; thus evidencing the empirical application of the motivation process in 65%, and 17% in the training and selection process; this, excluding the application of the recruitment processes, hiring, induction, motivation, performance evaluation, career development, hygiene, safety and quality of life and dismissal; resulting in an inefficient personnel management, and that is why the proposal of a management model for the above-mentioned company’s personnel based on the Chiavenato Human Talent Management model with its 9 sub-processes is made, all of this aiming to obtaining an ideal management of the company’s personnel and therefore enabling it to obtain competitive advantages in its surroundings, having human resources as its most relevant asset for its development and productivity as a company.